2006
DOI: 10.1002/pola.21358
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of photoluminescent and electrochemical properties of new aromatic polyamides and polyimides with a kink 1,2‐phenylenediamine moiety

Abstract: A series of novel triphenylamine‐containing aromatic polyamides and polyimides having a crank and twisted noncoplanar structures were synthesized in inherent viscosities of 0.14–0.64 dL/g and 0.11–0.67 dL/g, respectively. These polymers had useful levels of thermal stability associated with relatively high glass‐transition temperatures (174–311 °C). They exhibited strong UV–Vis absorption bands at around 300 nm in NMP solutions. The PL spectra of these polymers in NMP solutions (1 × 10−5 M) showed maximum peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 60 publications
(58 reference statements)
1
19
0
Order By: Relevance
“…Development of novel light‐emitting materials has been of particular interest for applications in optoelectronics. To achieve this goal, many neutral light‐emitting polymers have been developed,3 but there are a few examples that have a D‐A chemical architecture 4b, 14. Here, we demonstrated how a D‐A arrangement based on ambipolar moiety affects the optical properties of poly(pyridinium salt)s. The fluorescence of polymer solutions in neutral condition was too low to measure.…”
Section: Resultsmentioning
confidence: 85%
“…Development of novel light‐emitting materials has been of particular interest for applications in optoelectronics. To achieve this goal, many neutral light‐emitting polymers have been developed,3 but there are a few examples that have a D‐A chemical architecture 4b, 14. Here, we demonstrated how a D‐A arrangement based on ambipolar moiety affects the optical properties of poly(pyridinium salt)s. The fluorescence of polymer solutions in neutral condition was too low to measure.…”
Section: Resultsmentioning
confidence: 85%
“…In their reviewed articles, Shirota et al had identified a number of structural characteristics necessary to achieve a stable glassy state, while keeping high thermal stabilities 14. These structural designs have been applied successfully in both molecular14 and polymeric15 materials. The synthesized ionic polymers had high T g s as compiled in Table 3, similar to neutral polymers based on 4‐aryl‐2,6‐bis(4‐aminophenyl)‐pyridine 5–7.…”
Section: Resultsmentioning
confidence: 99%
“…In their reviews, Shirota et al2 outlines a few of the necessary structural conditions that would ensure a stable glassy state of a material. Liou et al3 had successfully demonstrated application on these structural characteristics by preparing a conjugated monomer having a crank and twisted noncoplanar moiety. Various low molecular weight, oligomeric and polymeric materials were explored as potential candidates for OLEDs 4.…”
Section: Introductionmentioning
confidence: 99%